Baga Dorbet Cycle of the Jangar Epic: Typical Passages as a Means to Identify the Taleteller’s Personality - Bayrta B. Mandzhieva (Oriental Studies, 2021)
Introduction. Russian folklorists have tended — and still do — to focus on formula-type language patterns inherent to traditional epic poetry. The shaping of epic songs would be facilitated by the wide use of structurally identical and stylistically similar descriptions and situations referred to as loci communes (‘typical passages’). Goals. The paper aims at identifying the personality of the taleteller to have recited the Baga Dorbet (Russ. Maloderbetovsky) cycle of the Jangar epic. With this in view, the work reveals typical passages of the Cycle, provides comparative insights into ones within prologues of the Cycle, compares the typical passages to similar elements from other cycles and individual repertoires. Materials and Methods. The study employs the methodology developed by P. D. Ukhov for the classification of Russian bylinas, and analyzes Jangar epic songs from the Baga Dorbet and Baga Tsokhor cycles, repertoires of such renown jangarchis as Eelyan Ovla, Mukӧvün Basangov, Dava Shavaliev, Nasanka Baldyrov, and Badma Obushinov. Conclusions. Typical passages of the Baga Dorbet cycle are structurally identical and stylistically homogenous descriptions where both syntactic patterns and described details and grammatical forms of parts of speech coincide which attests to that the texts were authored by (recorded from) one and the same taleteller. The opinion is confirmed by the below given examples of typical passages from other cycles that differ not only in terms of style or structure, but the very depicted objects, events, participants of the feast, the seating chart of theirs, and even numbers and sequence of stanzas significantly vary. The differences are determined by that the taletellers were representing different epic performance traditions with certain narrative patterns inherited from their predecessors. The comparative analysis of typical passages from the Baga Dorbet cycle shows the taleteller not only reproduces the once learnt song but rather creatively approaches every single performance maintaining standard elements of typical passages, modifies epic formulas employing synonyms, rearranging stanzas, reducing or adding details of descriptions, etc. This can be explained by that ‘above all in epic memory is not the formula precisely and intactly articulated in words but the artistic content, the taleteller (who) adheres to the framework of epic knowledge <...> (to) select one of the possible paths’, since this epic knowledge is wider than the text recited. So, the study concludes the whole of the Baga Dorbet cycle was recorded from (authored by) one taleteller and students whose names still remains unknown.